2006
DOI: 10.1177/10634266060140020201
|View full text |Cite
|
Sign up to set email alerts
|

Oppositional Defiant Disorder Rating Scale

Abstract: In this article, the authors report the psychometric properties of a parent-completed rating scale based on the criteria for oppositional defiant disorder (ODD) in the Diagnostic and Statistical Manual of Mental Disorders— Fourth Edition—Text Revision ( DSM-IV-TR). Mothers of 294 boys and 48 girls with attention-deficit/hyperactivity disorder (ADHD) and 53 boys and 45 girls without behavior problems completed the Oppositional Defiant Disorder Rating Scale (ODDRS). Fathers of 44 boys with ADHD also completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In addition, the study provides initial evidence for the factorial validity of teacher ratings of DSM-IV-TR-defined symptoms of ODD and CD in clinical populations. Since similar findings were reported for parent-completed symptom ratings [3,4,25,28], it can be concluded that DSM-based rating scales are useful instruments for assessing disruptive behavior problems in children and adolescents across different contexts.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In addition, the study provides initial evidence for the factorial validity of teacher ratings of DSM-IV-TR-defined symptoms of ODD and CD in clinical populations. Since similar findings were reported for parent-completed symptom ratings [3,4,25,28], it can be concluded that DSM-based rating scales are useful instruments for assessing disruptive behavior problems in children and adolescents across different contexts.…”
Section: Discussionsupporting
confidence: 52%
“…Many of these are directly linked to the diagnostic criteria of the Diagnostic and Statistical Manual of Mental Disorders (DSM) [1] or the ICD-10 Classification of Mental and Behavioural Disorders [2] and ask the respondent to rate the presence and intensity of symptoms of oppositional defiant disorder (ODD) and conduct disorder (CD). Although parent-completed symptom rating scales are reliable and valid measures of disruptive behavior [3,4], several authors recommended to use additional information from teachers when making diagnostic decisions concerning ODD/CD [5]. …”
mentioning
confidence: 99%
“…The eight-item ODDRS evaluates the degree to which mothers felt that each of the eight DSM-IV-TR ODD symptoms were characteristic of their child (Hommersen, Murray, Ohan, & Johnston, 2006). Mothers rated these behaviors on a 4-point Likert-type scale from not at all to very much.…”
Section: Methodsmentioning
confidence: 99%
“…. This scale is similar to the one proposed by Hommersen, Murray, Ohan, and Johnston (2006), and to the one used by Molina, Smith, and Pelham (2001) in a previous study. It basically consists in formulating the 8 statements of criterion A of the DSM-IV for the diagnosis of ODD, as questions.…”
Section: Oppositional Defiant Disorder Rating Scale Based On Dsm-iv (mentioning
confidence: 68%